Effect of surface -specific training on 20-m sprint performance on sand and grass surfaces - Binnie, M. J.; Peeling, P.; Pinnington, H.; Landers, G.; Dawson, B (The Journal of Strength and Conditioning Research, 2013)
This study compared the effect of an 8-week preseason conditioning program conducted on a sand (SAND) or grass (GRASS) surface on 20-m sprint performance. Twelve team-sport athletes were required to attend three 1-hour training sessions per week, including 2 surface-specific sessions (SAND, n = 6 or GRASS, n = 6) and 1 group session (conducted on grass). Throughout the training period, 20-m sprint times of all athletes were recorded on both sand and grass surfaces at the end of weeks 1, 4, and 8. Results showed a significant improvement in 20-m sand time in the SAND group only (p < 0.05), whereas 20-m grass time improved equally in both training subgroups (p < 0.05). These results suggest that surface-specificity is essential for 20-m speed improvements on sand and also that there is no detriment to grass speed gains when incorporating sand surfaces into a preseason program.